Effects of Geographic Region on the Composition of Bactrian Camel Milk in Mongolia - He, Jing (Animals (Basel), 2019)
SUMMARY: Camels are known to occupy arid and desert countries. These pastoralist areas and conditions make it difficult to estimate camel milk production. Camel milk is considered to have anti-cancer, hypo-allergic and anti-diabetic properties. A high content of unsaturated fatty acids contributes to its overall dietary quality. The low quantity of β-casein and the lack of β-lactoglobulin are linked to the hypo-allergic effect of camel milk. Although the Bactrian camel is an important domestic animal in Mongolia, few studies have focused on Bactrian camel milk in this country. Our study characterizes the amino acid and fatty acid compositions of Bactrian camel milk collected from several geographical areas in Mongolia. The findings establish a theoretical basis for additional studies on the composition of milk from Bactrian camels in Mongolia. ABSTRACT: Camel milk is considered as an essential source of nutrition for desert people. However, few studies have investigated how geography affects Bactrian camel milk in Mongolia. In this study, we evaluated the differences in gross composition, fatty acid composition, and amino acid composition among Bactrian camel milk samples collected from 102 Bactrian camels in five different Mongolian regions. The proportion of long-chain fatty acids, out of total fatty acids, was high in all samples of Bactrian camel milk. The primary fatty acids detected in the samples were palmitic acid (23.99–30.72%), oleic acid (17.21–24.24%), and stearic acid (11.13–16.49%), while the dominant amino acids were leucine, lysine, valine, and aspartic acid. Cysteine was the least common amino acid detected in the Bactrian camel milk samples. Considerable differences in the fatty acid and amino acid compositions were observed among Bactrian camel milk from different regions of Mongolia. The findings suggest that geography strongly affects the composition of camel milk.